2016
DOI: 10.17586/2220-8054-2016-7-3-482-487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precipitating agent NaOH on the preparation of copper oxide nanostructures for electrochemical applications

Abstract: Copper oxide (CuO) nanostructures with different concentrations of sodium hydroxide for electrochemical applications such as supercapacitors have been synthesized using a simple and low-cost precipitation method. X-ray diffraction pattern confirmed the formation of CuO nanostructures without any impurities and further confirmed its highly crystalline, single phase, monoclinic nature. UV-diffuse reflectance spectral (UV-DRS) studies provided the absorption edge of the material and the estimated band gap value f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The electrochemical studies confirm the capacitance behavior of nano structured materials [42]. Baby Sunitha et.al [28] reported that o-toluidine polymerized with Montmorillonite by chemical oxidation method using potassium perdisulfate shows good solubility in both DMSO and DMF and the intercalation of the polymer in between the Montmorillonite clay layers increase in the d-spacing.…”
Section: Cyclic Voltammetrysupporting
confidence: 61%
“…The electrochemical studies confirm the capacitance behavior of nano structured materials [42]. Baby Sunitha et.al [28] reported that o-toluidine polymerized with Montmorillonite by chemical oxidation method using potassium perdisulfate shows good solubility in both DMSO and DMF and the intercalation of the polymer in between the Montmorillonite clay layers increase in the d-spacing.…”
Section: Cyclic Voltammetrysupporting
confidence: 61%
“…It means that Na 2+ ions from the electrolyte have plenty of time to diffuse at a lower scan rate and can reach the highest surface area of the active material [2,8] . The literature review compared with present work is shown in Table 1 [2,9,12–18] …”
Section: Resultsmentioning
confidence: 88%
“…[2,8] The literature review compared with present work is shown in Table 1. [2,9,[12][13][14][15][16][17][18] Furthermore, the specific capacitance performance for C 1 , MC 2 , MC 4 , and MC 6 electrodes is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations